2008
DOI: 10.4161/cc.7.5.5485
|View full text |Cite
|
Sign up to set email alerts
|

Activating E17K mutation in the gene encoding the protein kinase AKT in a subset of squamous cell carcinoma of the lung

Abstract: Somatic mutation (E17K) that constitutively activates the protein kinase AKT1 has been found in human cancer patients. We determined the role of the E17K mutation of AKT1 in lung cancer, through sequencing of AKT1 exon 4 in 105 resected, clinically annotated non-small cell lung cancer specimens. We detected a missense mutations G→A transition at nucleotide 49 (that results in the E17K substitution) in two squamous cell carcinoma (2/36) but not in adenocarcinoma (0/53). The activity of the endogenous kinase car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
108
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(125 citation statements)
references
References 20 publications
7
108
2
6
Order By: Relevance
“…The observation appears to hold true in lung cancer were the AKT1 mutation was detected only once in squamous cell and not in adenocarcinoma samples. This is in accordance with a previous report (Malanga et al, 2008).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The observation appears to hold true in lung cancer were the AKT1 mutation was detected only once in squamous cell and not in adenocarcinoma samples. This is in accordance with a previous report (Malanga et al, 2008).…”
supporting
confidence: 83%
“…The AKT1 E17K mutation alters the electrostatic interactions of the pocket, activates AKT1 in a PI3K-independent manner, transforms rodent cells in vitro and can induce leukaemia in mice (Carpten et al, 2007). Until now AKT1 mutations have been reported in breast, colon, ovarian and lung cancer (Carpten et al, 2007;Malanga et al, 2008). Interestingly, in all the cases examined only one change (E17K) was detected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent evidence indicates that the molecular mechanism underlying activation of AKT1(E17K) is a broadened target lipid selectivity that allows high-affinity binding to PI(4,5)P2 (Landgraf et al, 2008). AKT1(E17K) mutation has been reported in various human cancers, including breast cancers, colorectal cancers, ovarian cancers, squamous cell carcinoma of the lung, endometrial carcinomas, urothelial carcinoma and bladder cancer, but not in other multiple human malignancies, including acute leukemias and liver cancers (Carpten et al, 2007;Kim et al, 2008;Mahmoud et al, 2008;Malanga et al, 2008;Mohamedali et al, 2008;Riener et al, 2008;Shoji et al, 2009;Zilberman et al, 2009;Askham et al, 2010). These studies suggested that AKT1(E17K) mutation occurs at a low frequency and in a tissue-specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of AKT1 mutations is only 1% reported in NSCLC but they have been identified only in squamous cell carcinomas [66,67].…”
Section: Akt Mutationsmentioning
confidence: 99%